Dynamics of the Lithiation and Sodiation of Silicon Allotropes: From the Bulk to the Surface. Issue 7 (2nd June 2017) - Marzouk, Asma; Soto, Fernando A.; Burgos, Juan Carlos; Balbuena, Perla B.; El-Mellouhi, Fedwa
Abstract : This work investigates two silicon allotropes, Si24 -4c and Si24 -8c as anode materials for LIBs and NIBs that have the potential to meet the challenging properties of cost, electronic conductivity, and lifetime. Density Functional Theory and Ab-initio Molecular Dynamics studies of the silicon allotropes' surfaces provide new insights into the most probable surface chemistries, lithiation, sodiation, initial stages of SEI formation, saturation limit of the allotrope and ionic diffusion. These Si allotropes, considered as promising anode materials, are characterized by a small volume expansion after a full ionic insertion which favors the stability of the capacity. The ionic diffusion analysis for the migration pathways of the Li and Na-ions reveal that the Na-ion diffuses better within the allotrope Si24 -4c. However, the allotrope Si24 -8c is found to be most appropriate for Li-ion regarding diffusion barrier and specific capacity.